Integrated Ideas of a Life Warrior An Interview with Leo Fong - Hobart, Peter (Revista de Artes Marciales Asiáticas, 2012)
Mr. Leo Fong is the architect and founder of a system of martial arts known as Wei Kuen Do (man. Hui Quan Dao)—the Way of the Integrated Fist. Leo Fong trained in a variety of Chinese disciplines, including Shaolin, Choy Lay Fut and Tiger Claw, and was a close associate of Bruce Lee. Over the course of his studies, Master Fong combined many of the aspects of Chinese martial arts with principles of western boxing, to produce his own, unique and devastating system of self-defense.